Moho depth map of northern Venezuela based on wide-angle seismic studies. (April 2021) - Schmitz, Michael; Ramírez, Keyla; Mazuera, Fernando; Ávila, Jesús; Yegres, Luis; Bezada, Maximiliano; Levander, Alan; ,
Abstract: As part of the lithosphere, the crust represents Earth's rigid outer layer. Some of the tools to study the crust and its thickness are wide-angle seismic studies. To date, a series of seismic studies have been carried out in Venezuela to determine in detail the crustal thickness in the southern Caribbean, in the region of the Caribbean Mountain System in northern Venezuela, as well as along the Mérida Andes and surrounding regions. In this study, a review of the wide-angle seismic data is given, incorporating new data from the GIAME project for western Venezuela, resulting in a map of Moho depth north of the Orinoco River, which serves as the basis for future integrated models. Differences in Moho depths from seismic data and receiver function analysis are discussed. From the Caribbean plate, Moho depth increases from 20 to 25 km in the Venezuela Basin to about 35 km along the coast (except for the Falcón area where a thinning to less than 30 km is observed) and 40–45 km in Barinas - Apure and Guárico Basins, and Guayana Shield, respectively. Values of more than 50 km are observed in the Maturín Basin and in the southern part of the Mérida Andes.